2022
DOI: 10.3390/s22176502
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Evaluation of the Scapular Skin Marker Movements in the Upright Posture

Abstract: Motion capture systems using skin markers are widely used to evaluate scapular kinematics. However, soft-tissue artifact (STA) is a major limitation, and there is insufficient knowledge of the marker movements from the original locations. This study explores a scapular STA, including marker movements with shoulder elevation using upright computed tomography (CT). Ten healthy males (twenty shoulders in total) had markers attached to scapular bony landmarks and underwent upright CT in the reference and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Nakano et al (2020) reported even higher errors during throwing with up to 47.3 mm for elbow joint center with equivalent method and materials. Comparably, marker movement distance for scapula markers in elevated position ranged from 30.4 to 70.0 mm (Yoshida et al 2022). Considering our results were preliminary work on uniform population, they highlighted the potential of accuracy and versatility of our method if the improvements raised are addressed and applied to a more diverse cohort.…”
Section: Resultsmentioning
confidence: 68%
“…Nakano et al (2020) reported even higher errors during throwing with up to 47.3 mm for elbow joint center with equivalent method and materials. Comparably, marker movement distance for scapula markers in elevated position ranged from 30.4 to 70.0 mm (Yoshida et al 2022). Considering our results were preliminary work on uniform population, they highlighted the potential of accuracy and versatility of our method if the improvements raised are addressed and applied to a more diverse cohort.…”
Section: Resultsmentioning
confidence: 68%
“…This approach could effectively mitigate the effects of soft tissue artifacts (STAs). In systems using skin-mounted markers, STAs are typically present and challenging to eliminate due to the inherent mismatch between skin and bone movement [ 28 , 29 , 30 ]. For instance, the reported accuracy of such systems for walking motion tasks shows average errors up to 4.40° and 13.0 mm for rotations and translations, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%